Dersú Uzalá - Arsenʹev, V. K. (Vladimir Klavdievich), 1872-1930; Arsenʹev, V. K. (Vladimir Klavdievich), 1872-1930.; Hernández Ranera, Sergio; Sanz Redondo, Rubén. (Tres Cantos, Madrid, España : Ediciones Akal, S.A., 2011)
Arseniev describes three explorations in the Ussurian taiga along the Sea of Japan above Vladivostok, beginning with his first encounter of the solitary aboriginal hunter named Dersu, a member of the Gold tribe, who thereafter becomes his guide. Each expedition is beset with hardship and danger: through blizzard and flood and assorted deprivations, these two men forge an exceptional friendship in their mutual respect for the immense grandeur of the wilderness. But the bridges across language, race and culture also have limitations, and the incursion of civilization exacts its toll. Dersu the Trapper is at once a witnessing of Russia's last frontier and a poignant memoir of rare cross-cultural understanding.
Online resource; title from ePub title page (Digitalia, viewed January 9, 2017)
Keywords: Ussuri River Valley (Russia and China) -- Description and travel; Natural history -- Ussuri River Valley (Russia and China); Dersu Uzala; Arsenʹev, V. K. -- 1872-1930 -- Travel -- Ussuri River Valley (Russia and China); Electronic books